Konsepsi Aktualisasi Diri untuk Mencapai Derajat Ihsan: Studi Penafsiran QS. Ar-Rahman Ayat 60 dengan Pendekatan Ma’na Cum Maghza - Nurfadilah Nurfadilah; Sumanta Sumanta; Muhammad Maimun; Mohamad Yahya; Muhamad Zaenal Muttaqin (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the conception of self-actualization to achieve the degree of ihsan through the study of the interpretation of the QS. ar-Rahman verse 60 with approach ma'na cum maghza. This study uses a qualitative method with content analysis. The formal object of this study is the interpretation QS. ar-Rahman verse 60 with approach ma'na cum maghza, while the material object of self-actualization conception reaches the degree of ihsan. The scope of this study is the interpretation of the Qur’an. The results and discussion in this study indicate that self-actualization is necessary to achieve the degree of ihsan based on the interpretation of QS. ar-Rahman verse 60 with approach ma'na cum maghza. This study concludes that the interpretation of QS. ar-Rahman verse 60 with approach ma'na cum maghza can reflect the conception of self-actualization to achieve the degree of ihsan. This study recommends educators, especially in Islamic institutions, to apply the concept of self-actualization as an effort to achieve the degree of ihsan based on QS. ar-Rahman verse 60, so that every human being can strive for optimal virtues.